GE_GERICHTE P/15156/2016 vom 6. November 2020 - GE Cour de justice (2020)
DIFFAMATION;INJURE;LIBERTE SYNDICALE;CONTRAINTE(DROIT PÉNAL);MENACE(DROIT PÉNAL);FRAIS DE LA PROCÉDURE | CP.173; CP.177; CP.181; CP.180; CO.49; CPP.420.al2